Prophylactic paclitaxel-eluting stent placement does not improve covered femoropopliteal stent patency - Rory Marples, MBBS (Elsevier, 2022)
Objective: Covered stents are an important tool in managing femoropopliteal peripheral arterial disease. However, their performance is impaired by edge neointimal hyperplasia and restenosis. We examined the effectiveness of prophylactic deployment of paclitaxel-eluting stents to prevent edge restenosis. Methods: A retrospective case–control study was performed. Patients with femoropopliteal peripheral arterial disease who were treated with Viabahn stent placement were compared to patients treated with Viabahn stents deployed in conjunction with paclitaxel-eluting stents (PTX). The primary outcome was time to loss of stent primary patency. The Kaplan–Meier method was used. Results: A total of 36 Viabahn and 25 Viabahn + paclitaxel-eluting stent procedures were evaluated, with mean follow-up periods of 27 and 18 months, respectively. The Viabahn + paclitaxel-eluting stent group had a longer length of vessel stented (P = .0023). Twelve-month primary patency was 74% in the Viabahn group and 75% in the Viabahn + paclitaxel-eluting stent group. Pre-existing dyslipidemia correlated with earlier loss of primary patency across the combined cohort (P = .0193). Conclusion: Viabahn stent primary patency is unaffected by the addition of paclitaxel-eluting stents.